PENGEMBANGAN MODEL MANAJEMEN PENDIDIKAN OLAHRAGA BERBASIS ARTIFICIAL INTELLIGENCE (AI) UNTUK MENINGKATKAN EFEKTIVITAS PEMBELAJARAN - Syahru Ramadhan; Usni Khamsur Ramadhan; Indah Lestari (Universitas Jabal Ghafur, 2026)
This study aims to develop the Artificial Intelligence Sport Education Management Model (AI-SEMM) as a sport education management model that integrates Artificial Intelligence (AI) technology to enhance learning effectiveness through data-driven management. The study employed a Research and Development (RD) approach using the ADDIE development model, consisting of the Analysis, Design, Development, Implementation, and Evaluation stages. Data were collected through a literature review, observations, interviews, questionnaires, documentation, Focus Group Discussions (FGDs), and expert validation involving specialists in educational management, sport education, and Artificial Intelligence. Data were analyzed qualitatively using the Miles, Huberman, and Saldaña interactive model and quantitatively through descriptive analysis, content validity testing, and instrument reliability testing. The findings resulted in the development of the AI-SEMM, which consists of five main components: AI Planning, AI Organizing, AI Learning Implementation, AI Monitoring and Evaluation, and AI Decision Support. The model integrates learning analytics, machine learning, and decision support systems to support planning, implementation, monitoring, evaluation, and decision-making processes in a more effective, efficient, objective, and data-driven manner. This study concludes that AI-SEMM is an innovative model with the potential to improve the effectiveness of sport education learning management and serve as an alternative framework for schools in supporting digital transformation and enhancing learning quality.